2012
DOI: 10.1128/jvi.06042-11
|View full text |Cite
|
Sign up to set email alerts
|

The NK Cell Response to Mouse Cytomegalovirus Infection Affects the Level and Kinetics of the Early CD8+T-Cell Response

Abstract: Natural killer (NK) cells and CD8 ؉ T cells play a prominent role in the clearance of mouse cytomegalovirus (MCMV) infection.The role of NK cells in modulating the CD8 ؉ T-cell response to MCMV infection is still the subject of intensive research. For analyzing the impact of NK cells on mounting of a CD8 ؉ T-cell response and the contribution of these cells to virus control during the first days postinfection (p.i.), we used C57BL/6 mice in which NK cells are specifically activated through the Ly49H receptor e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
115
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 79 publications
(130 citation statements)
references
References 54 publications
12
115
1
1
Order By: Relevance
“…1C). We selected these three strains because past work using depleting Abs against NK cells demonstrated that NK cell function was critical for controlling MCMV infection in all three strains (34)(35)(36)(37).…”
Section: Control Of MCMV Infection Is Not Dependent On Ncr1mentioning
confidence: 99%
“…1C). We selected these three strains because past work using depleting Abs against NK cells demonstrated that NK cell function was critical for controlling MCMV infection in all three strains (34)(35)(36)(37).…”
Section: Control Of MCMV Infection Is Not Dependent On Ncr1mentioning
confidence: 99%
“…Thus, treatment with the anti-CD25 antibody may have also depleted NK cells, whereas in our approach, only Foxp3 ϩ Tregs were ablated. Depletion of NK cells has been shown to enhance mCMV titers and mCMV-specific T cell responses during acute mCMV infection (22)(23)(24)(25)(26), which might be the reason for the strong effect reported by Arens et al (20). Unlike with mCMV, the expansion of Tregs has been found in mice infected with other herpesviruses, like herpes simplex virus (HSV) (12,27).…”
Section: Fig 3 Mcmv-specific Cd8mentioning
confidence: 99%
“…Even though NK cell killing of MCMV-infected cells allows for rapid control of viral spread, it reduces the availability of APC and limits the length and potency of virus-specific adaptive T cell responses as evidenced by Andrews et al (34) or Mitrović et al (35). Therefore, strong innate immune responses might have detrimental effects on long lasting adaptive immunity.…”
Section: Discussionmentioning
confidence: 99%